(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Non-alcoholic fatty liver disease (NAFLD), a growing global epidemic, encompasses a broad spectrum of stages of disease severity, including simple steatosis, steatohepatitis (NASH), and cirrhosis. Accurate staging is necessary for the treatment and follow-up of the patients. Several non-invasive methods for the objective assessment of disease severity in NAFLD have been tested; serum ferritin is relatively new. Therefore, the objective of the study was to evaluate the correlation between the variation of serum ferritin levels and different histological stages of NAFLD. Methods: The study was a hospital-based cross-sectional observational study conducted at the Department of Medicine and Hepatology, DMCH, from July 2017 to December 2017. All adult patients of NAFLD admitted or attended outdoors in the aforementioned department were approached for inclusion in the study. Assessment of the patients was done by the NAFLD Activity Score (NAS), and fibrosis staging and estimation of serum ferritin were also performed for each patient. Written informed consent was taken from the subject, and ethical issues were addressed. Following data collection, it was analyzed by the SPSS 17. Results: Out of a total of 50 patients, 60% were males and 40% were females (M: F=3:2). Mean age was 49.22±9.30 SD (years), ranging from 33 to 65 years. About 46% had class I obesity, 26% were overweight, and 8% had class II obesity. The majority of patients (62%) had NASH, 34% had borderline NASH, and 4% had no signature of NASH in the histopathology. The mean NAFLD activity score (NAS) was 4.98±1.47. Of all, 46%, 40%, and 10% of patients were in fibrosis stages 2, 1, and 3, respectively. Mean serum ferritin was 226.47±155.70 SD (ng/ml) [range: 13.60-722.00 ng/ml with a median value of 186.00 ng/ml]. Serum ferritin level was slightly higher in patients with NASH stage on histopathology than in those with borderline NASH stage and non-NASH stage. Similarly, the mean serum ferritin level was found to increase slightly with increasing fibrosis score. However, in both cases, the relationship is not statistically significant (p-value>0.05). Conclusion: Serum ferritin level is not associated with different histological stages of Non-alcoholic fatty liver disease. Bangladesh J Medicine 2026; 37(2): 114-120